Caught in organized ambivalence: institutional complexity and its implications in the German hospital sector. Issue 4 (21st April 2017) - Bode, Ingo; Lange, Johannes; Märker, Markus
ABSTRACT: Worldwide, public service-providing organizations confront regulatory hybridization. While their societal mission persists, they are expected to become more business-like. Drawing on theory concerned with institutional complexity and ambivalence in organizations, this article illuminates the case of German acute care hospitals. We depict the emergence of market orientation in this industry, its structural impact and major sensemaking patterns at the site level. In our multiple case study, we find 'organized ambivalence' shaping the institutional context and affecting the undertakings' internal life. Thus, regulatory hybridization tends to create certain traps – which challenges ideas according to which it helps improve public management.